The impact of social media onthe influence of inventory management on customer satisfaction. A case study of mukwano group of companies the financial decisions of students at Uganda Christian university - SIFA KUBALEZAGA NADEGE (Uganda Christian University, 2026)
This study examined the influence of inventory management on customer satisfaction at Mukwano Group of Companies. The general objective was to assess the effect of inventory management practices on customer satisfaction, guided by three specific objectives: to examine the effect of inventory accuracy on customer satisfaction, to assess the effect of inventory order fulfillment and product availability on customer satisfaction, and to evaluate the impact of inventory control practices on customer satisfaction. A descriptive cross-sectional research design was adopted using both quantitative and qualitative approaches. Data were collected at one point in time from a sample of 80 respondents selected from a population of 100, determined using Krejcie and Morgan’s (1970) sample size table. The subjects who participated in this study included logistics and warehousing workers, production and supply chain workers, and retail customers. Simple random sampling and purposive sampling techniques were employed. Data collected through the use of structured questionnaires was classified as quantitative, whereas data collected through interviews with managers and supervisors were classified as qualitative. Quantitative data was analyzed using descriptive statistics such as frequencies, percentages, means, and standard deviations, using SPSS software. From the findings of the research, it is evident that an accurate inventory helps increase customer satisfaction by ensuring the availability of goods, reducing incidences of out-of-stock situations, receiving fewer complains, and completing orders reliably. It is also worth noting that one of the discoveries from this study is the presence of a positive relationship between the completion of orders on time, product availability, and customer satisfaction. Order delays and stockouts have been found to affect customer satisfaction and loyalty negatively. In addition, it was noted that effective inventory management was one of the key elements that played a vital role in influencing customer satisfaction. In particular, the study recommended the use of computerized inventory management techniques, improved techniques of predicting demand, conducting inventory audits, as well as improving the level of training for the employees. These findings contribute to the existing literature on the impact of inventory management on customer satisfaction in Uganda.
Undergraduate